2016
DOI: 10.1007/s00428-016-1935-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of implementing synoptic pathology reporting in cancer diagnosis: a systematic review

Abstract: Pathology reporting is evolving from a traditional narrative report to a more structured synoptic report. Narrative reporting can cause misinterpretation due to lack of information and structure. In this systematic review, we evaluate the impact of synoptic reporting on completeness of pathology reports and quality of pathology evaluation for solid tumours. Pubmed, Embase and Cochrane databases were systematically searched to identify studies describing the effect of synoptic reporting implementation on comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 48 publications
8
94
0
4
Order By: Relevance
“…As synoptic reporting, compared to narrative reporting, results in an increased overall completeness of pathology reports, and as it enables easy data extraction because all variables are stored in a standardized manner, data included in this study were solely from synoptically reported IBC lesions. Currently, over 80 percent of (pre)malignant breast lesions is reported via the synoptic PALGA protocol by pathologists in the Netherlands .…”
Section: Discussionsupporting
confidence: 87%
“…As synoptic reporting, compared to narrative reporting, results in an increased overall completeness of pathology reports, and as it enables easy data extraction because all variables are stored in a standardized manner, data included in this study were solely from synoptically reported IBC lesions. Currently, over 80 percent of (pre)malignant breast lesions is reported via the synoptic PALGA protocol by pathologists in the Netherlands .…”
Section: Discussionsupporting
confidence: 87%
“…In varied settings, including thyroid cancer and pancreatic cancer, synoptic reporting has been examined by international studies and validated as a method for capturing clinical data and improving patient outcomes. [29][30][31] Technological advances have made ultrasonography more accessible, and surgeon-directed assessments are now significantly more likely to drive interventions. 32,33 In fact, the lack of standardized reporting is driving the increased uptake of ultrasonog raphy among surgeons owing to the varied quality of reports, and this trend is accelerating.…”
Section: Discussionmentioning
confidence: 99%
“…What started as a basic TB e‐form gradually expanded to include granular details but was specifically kept from being unwieldy by using branching logic for specific entries and limiting free‐text sections. Synoptic reporting has replaced traditional free‐text to ensure the repeated completeness of data documentation in a consistent scientific format and has gained acceptance in various fields, such as radiology, pathology, and operative surgery . It was hence a logical reporting choice to guide TB data entry due to the complexity of HNC patient data.…”
Section: Discussionmentioning
confidence: 99%